1991
DOI: 10.1590/s0074-02761991000400004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deltamethrin spraying on the sandfly populations in a focus of American cutaneous leismaniasis

Abstract: The effect of deltamethrin of the sandfly population in a focus of American Cutaneous Leishmaniasis in Viana, Espírito Santo State is described. The phlebotomine population density was determined inside and outside houses during a one year period in a treated and untreated area. The results showed a significant reduction in the number of sandflies inside houses in the treated area compared with both the untreated area and the same area before spraying. Despite having a residual action for 12 months after spray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 0 publications
1
19
0
5
Order By: Relevance
“…IRS is not expected to impact on exophilic and exophagic vectors, nor immature stages; though sandfly breeding sites are largely unknown (Alexander and Maroli, 2003). Measurable entomological indicators of control success include reductions in human landing rates, blood-feeding success, or human blood index, and reduced vector survival (lower parous rates), as demonstrated for a wide range of New World (Davies et al, 2000;Feliciangeli et al, 2003a,b;Courtenay et al, 2007;Falcao et al, 1991), and Old World sandfly species (Benzerroung et al, 1992;Reyburn et al, 2000;Joshi and Rai, 1994;Kaul et al, 1994;Mukhopadhyay et al, 1996;Joshi et al, 2009). Insecticide deterrency (sometimes called repellency cf.…”
Section: Vector Controlmentioning
confidence: 99%
“…IRS is not expected to impact on exophilic and exophagic vectors, nor immature stages; though sandfly breeding sites are largely unknown (Alexander and Maroli, 2003). Measurable entomological indicators of control success include reductions in human landing rates, blood-feeding success, or human blood index, and reduced vector survival (lower parous rates), as demonstrated for a wide range of New World (Davies et al, 2000;Feliciangeli et al, 2003a,b;Courtenay et al, 2007;Falcao et al, 1991), and Old World sandfly species (Benzerroung et al, 1992;Reyburn et al, 2000;Joshi and Rai, 1994;Kaul et al, 1994;Mukhopadhyay et al, 1996;Joshi et al, 2009). Insecticide deterrency (sometimes called repellency cf.…”
Section: Vector Controlmentioning
confidence: 99%
“…In 2001 average captures in 1996-1997and 1997-1998Numerosos trabalhos de controle de flebotomíneos têm dado um enfoque para o uso de inseticidas químicos em paredes de casas e anexos (abrigos de animais, silos) 3,4,5,6,7,8,9 , em ambientes silvestres 10,11,12 e impregnados em mosquiteiros 13,14,15,16,17 . Essas medidas apesar de atrativas não são permanentes 18 , além do que, a precariedade das habitações, a descontinuidade e/ou o uso em épocas inapropriadas e os riscos ambientais advindos da aplicação de inseticidas em ambientes silvestres, constituem fatores limitantes para o controle de flebotomíneos 15,19,20,21 .…”
unclassified
“…Although some studies reported deltamethrin residual effects up to 9-12 months inside houses 13,19 , strong anti-feeding effects when applied to dogs as collars or topically, and repellent effects in impregnated bednets 7,8,9 , and pyrethroids as lambdacyalothrin reducing impact on Lu. longipalpis sand fly captures after focal or indoor applications 14,18 , there are many reports about the short or transient effects of fenitrothion 14 , cypermethrin 12 and deltamethrin as peridomestic sprayed insecticide 1,13,22,36 . Unfortunately the effects of insecticides for longer periods than 14 days could not be assessed in this study due to an abrupt change in the weather conditions that reduced the population; both in the intervention and the control group, but the results obtained were consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%